ANALISIS KUALITAS PENCAHAYAAN DAN AKUSTIK PADA BANGUNAN GEREJA KATEDRAL - Khuluk, Nazaruddin; Nikson, Wifan (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2020)
Church is a human need, architecture accommodates worship activities with worship buildings in architecture not only means being able to accommodate worship activities, but must have a great value, for example by displaying ceilings and pillars that are very high and impressive. Buildings that have a much larger proportion than the proportion of the human body willstimulate feelings that make humans feel very small. This feeling isdeliberately presented and often found in the design of places of worship,making people who are inside feel small and are exposed to something bigger.This feeling of "small" before God can be formed through the height of theceiling and towering elements (verticalism), natural lighting that enters throughthe gaps in the high plane (shroud), and material covering the spatialelements in the church that are able to condition the space. so that it looksopen and people will feel comfortable in it (transparent) (Mangunwijaya, 1992).Keywords: Lighting, Acoustics